ENDOTHELIAL NITRIC OXIDE SYNTHASE GENE INTRON- 4 27BP REPEAT POLYMORPHISM IS NOT ASSOCIATED WITH RHEUMATOID ARTHRITIS AMONG ASIAN INDIANS - CHINGKHEILEMBA MAYANGLAMBAM; UMA KUMAR; KUNZANG CHOSDOL; NIBHRITI DAS (International Journal of Pharma and Bio Sciences, 2014)
The aim of this study was to investigate the association of intron- 4 27bp repeat polymorphism in the endothelial nitric oxide synthase (eNOS) gene with rheumatoid arthritis (RA) in Asian Indians. A case control study in which 100 patients diagnosed with RA and 100 healthy controls were enrolled. DNA was extracted from peripheral blood and eNOS polymorphism was detected by PCR. All study participants were screened for nitric oxide (NO).Allelic and genotypic distribution did not differ significantly between RA patients and healthy control subjects. Reduced NO levels was detected in patients as compared to controls. Patients with bb genotype and ab genotypes were found to have significantly lower level of plasma NO as compared to controls with the same types of genotypes. eNOS gene intron- 4 27bp repeat polymorphism is not associated with the susceptibility to RA in Asian Indians.